Caspase Recruitment Domain Protein 6 Protects Against Hepatic Steatosis and Insulin Resistance by Suppressing Apoptosis Signal–Regulating Kinase 1. Issue 6 (15th November 2018) - Sun, Peng; Zeng, Qiang; Cheng, Daqing; Zhang, Kuo; Zheng, Jilin; Liu, Yupeng; Yuan, Yu‐Feng; Tang, Yi‐Da
Abstract : The rapidly increasing prevalence of metabolic disorders associated with nonalcoholic fatty liver disease (NAFLD) warrants further study of the underlying mechanisms to identify key regulators as targets for the development of therapeutic interventions. Caspase recruitment domain protein 6 (Card6), as a member of the CARD family that regulates cell death and immunity, may potentially control this process. Indeed, Card6 down‐regulation was found to be closely associated with the fatty livers observed in NAFLD patients, obese mice, and a palmitate‐treated hepatocyte model. Gain‐of‐function and loss‐of‐function Card6 mouse models demonstrated that Card6 protected mice from insulin resistance, hepatic steatosis, and inflammatory responses upon high‐fat diet administration. Mechanistically, Card6 interacted with and inhibited apoptosis signal–regulating kinase 1 (Ask1) and its subsequent downstream c‐Jun N‐terminal kinase/p38 signaling. Furthermore, Ask1 was sufficient to mediate Card6 function, and the interaction between Ask1 and Card6 was absolutely required for Card6 function in vivo . Adenovirus‐mediated Card6 overexpression in the liver effectively ameliorated insulin resistance and hepatic steatosis in ob/ob mice. Therefore, we identified Card6 as an important negative regulator in NAFLD. Conclusion: Targeting Ask1 by Card6 may be a good strategy to develop a therapeutic method against NAFLD.